CONTROL OF MANAGEMENT IN AN ORGANIZATION - Mr. Irfan Bashir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Current research proposes that there is impressive enthusiasm among researchers to coordinate other worldliness into work environment. One hole in the writing relates to the management control in associations with an assortment of spiritually-oriented representatives (spiritually charged association); its paper fills this hole. This applied paper utilizes "hermeneutic methodology" by looking into and deciphering spiritual writing, applying chosen ideas to the current working environment and structuring the management control framework to line up with the estimations of such associations. This conceptualizes spiritually from viewpoints of the significant ideas of "Nishkama Karma and Dharma". This paper offers a position that management control procedure would be distinctive in the spiritually charged association where representatives are probably going to be naturally persuaded and the company's qualities and objectives would speak to the virtues of its workers. It contend that work environment spirituality ought to be considered a significant possibility factor for hierarchical management, in specific identified with making do in view of the idea of Dharma. At long last, it talk about transformational administration rehearses, for example, rousing a mutual vision, which are reliable with the idea of such associations